Utility and Feasibility of Transcutaneous Spinal Cord Stimulation for Patients With Incomplete SCI in Therapeutic Settings: A Review of Topic - Martin, Rebecca (Frontiers in Rehabilitation Sciences, 2021)
Transcutaneous Spinal Cord Stimulation (TSCS) has been shown to enhance the excitability of spinal neural circuits. This excitation is associated with enhanced voluntary performance in patients with incomplete SCI (iSCI). Though there is much we do not know, combining this altered state of exciability with therapy has the potential to enhance the outcomes associated with activity-based interventions. It is a promising tool to augment the work being done in therapeutic settings with the potential to expedite recovery. There is, however, a lag in assimilating the science for clinical practice. This article will examine current literature related to the application of TSCS in combination with therapeutic interventions for motor recovery and aims to elucidate trends in waveform selection, duration and frequency, and combinatorial therapies that may inform clinical practice. With specific consideration for therapeutic settings, potential benefits, applications, and pitfalls for clinical use are considered. Finally, the next steps in research to move toward wider clinical utility are discussed.